IMPACTOS E DESAFIOS DA NEGLIGÊNCIA FAMILIAR NA EDUCAÇÃO E NO DESENVOLVIMENTO INFANTIL (REMUNOM, 2025)
This study investigated the impacts and challenges of family neglect in early childhoodeducation, using a bibliographic methodology. Neglect occurs when there is mistreatment and theomission of basic care, and is a serious social problem. Family neglect is a phenomenon that is oftensilent and difficult to identify, which makes addressing it even more challenging. For example,children can develop anxiety disorders, learning difficulties and self-esteem problems, and theseconsequences can last a lifetime. Given this worrying scenario, it is concluded that it is essential toimplement a multidisciplinary preventive approach. This involves collaboration between familymembers, educators and health professionals to identify signs of neglect and provide the necessarysupport to children at risk. Awareness programs on the importance of adequate care duringchildhood are essential to promote a healthy and safe environment for children's development. Onlythrough a joint effort will it be possible to ensure more effective teaching and learning, providingchildren with the necessary opportunities to grow up healthy and happy.